Comparative analysis of sialendoscopy, sonography, and CBCT in the detection of sialolithiasis. (24th October 2014) - Schwarz, David; Kabbasch, Christoph; Scheer, Martin; Mikolajczak, Stefanie; Beutner, Dirk; Luers, Jan C.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The diagnosis of sialolithiasis is, along with clinical presentation, based on different imaging techniques and more invasive procedures such as sialendoscopy. The aim of the study was to analyze the potential of cone beam computed tomography (CBCT) for the diagnosis of sialolithiasis and to compare the results with those of sonography and sialendoscopy. Study Design Retrospective analysis. Methods The data of 43 patients with suspected sialolithiasis were evaluated retrospectively. All patients had CBCT and sonographic imaging and received sialendoscopy to confirm and possibly treat sialolithiasis. Results Sonography, CBCT, and sialendoscopy together indicated sialolithiasis in 33 patients. The mean maximum diameter of the extracted sialoliths did not significantly differ between the three diagnostics. Each diagnostic tool showed an excellent specificity and positive predictive value. Sensitivity and negative predictive value were best in sialendoscopy (94% resp. 83%), followed by CBCT (79% resp. 56%) and then sonography (70% resp. 47%). Conclusion The results revealed that CBCT is capable of diagnosing sialoliths in general and tended to be more sensitive than sonography. However, in view of the radiation exposure, the use of CBCT must be critically weighed and should not be used as a primary option. Level of Evidence 4. Laryngoscope, 125:1098–1101, 2015